2013
DOI: 10.1021/bc400105j
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Fate in Plasma of Gadolinium Incorporated into High-Density Lipoproteins Used for Magnetic Imaging of Atherosclerotic Plaques

Abstract: We have previously reported enhancing the imaging of atherosclerotic plaques in mice using reconstituted high density lipoproteins (HDL) as nanocarriers for the MRI contrast agent gadolinium (Gd). This study focuses on the underlying mechanisms of Gd delivery to atherosclerotic plaques. HDL, LDL, and VLDL particles containing Gd chelated to phosphatidyl ethanolamine (DTPA-DMPE) and a lipidic fluorophore were used to demonstrate the transfer of Gd-phospholipids among plasma lipoproteins in vitro and in vivo. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…To determine that the paramagnetic and fluorescent dHDL and sHDL particles are specifically uptaken by J774A.1 macrophages and not a result of lipid exchange [ 35 ], we labeled the oxidized synthetic apo A-I H4 peptide using Dylight 488. We hypothesized that if uptake is specific, the Dylight 488-labeled oxidized Apo-AI H4 peptide along with the Rhodamine B-labeled lipid would be observed inside the cell.…”
Section: Resultsmentioning
confidence: 99%
“…To determine that the paramagnetic and fluorescent dHDL and sHDL particles are specifically uptaken by J774A.1 macrophages and not a result of lipid exchange [ 35 ], we labeled the oxidized synthetic apo A-I H4 peptide using Dylight 488. We hypothesized that if uptake is specific, the Dylight 488-labeled oxidized Apo-AI H4 peptide along with the Rhodamine B-labeled lipid would be observed inside the cell.…”
Section: Resultsmentioning
confidence: 99%
“…These types of GBCA-HDL mimicking NPs also showed in vivo efficacy in ApoE −/− mouse models [24]. Additionally, later in 2013, the same group conducted a study for clarifying the mechanism of using the Gd-HDL mimicking NPs for delivering Gd to the plaque and their fate in plasma [60]. In vitro and in vivo studies indicated that the possible delivery mechanism was that the Gd-DTPA-DMPE could be spontaneously transferred to the endogenous phospholipids and then cleared from the plasma [60].…”
Section: Hdl Mimicking Nps As Imaging Contrast and Theranostic Agentsmentioning
confidence: 99%
“…We have shown that HDL nanobiologics can be modified for their visualization using different imaging techniques, namely, optical imaging ,, (Figure A), MRI ,,, (Figure B), CT , (Figure C), and PET , (Figure D). Each modality has its own strengths .…”
Section: Diagnosticsmentioning
confidence: 99%